ANALISIS CYBER LAW DALAM PEMBERANTASAN CYBER TERORISM DI INDONESIA - Eka Lusyanti Marpaung; Mila astuti; Ali Ibrahim (Annual Research Seminar (ARS), 2017)
ABSTRACT-Computer crimes need to be aware of terrorist acts committed through this cyberspace. This allows it to happen in cyberspace just way different from the conventional acts of terrorism that exist in the real world but the effect can be felt also in the real world. this analysis is a research that is juridical-normative. To collect the necessary materials, the writer has been using literature research method, that is by studying law books, articles covering legal issues, the set of laws and regulations applicable in Indonesia, as well as various other written sources. The result of the research shows how to formulate offense against the criminal act of cyber terrorism in accordance with the positive law in Indonesia and how the application of Indonesian positive law to the criminal act of cyber terrorism. First, the offense on Law no. 15 of 2003 on Combating Terrorism Crime and Law Number 11 Year 2008